(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The relationship between race and language is deeply intertwined, influencing social identity, power structures, and cultural perceptions. Language often serves as a marker of racial identity, shaping how individuals are perceived and treated within society. This article explores the ways in which language reinforces racial hierarchies, the impact of linguistic discrimination, and the role of language in both marginalization and empowerment. By examining historical and contemporary perspectives, this discussion highlights the unsettling intersections of race and language in a globalized world.